Papers of Shirley Kral - Kral, Shirley (1958)
MS 5652 includes clippings, correspondence, notes, reports, leaflets relating to womens' issues. There are seminar papers for the Abortion Seminar held at A.N.U. 1971, newspaper clippings relating to abortion law reform, newsletters and information sheets of the Women's Electoral Lobby (ACT) and various cuttings, leaflets and some correspondence relating to women's issues. Later additions to the collection include publications, clippings, reports, notes, submissions, texts of speeches relating to Women and Politics Conference -1975, women's studies women's liberation movements, United Nations Decade for Women Conference, 1979, abortion, Women's Electoral Lobby and careers for girls. Material on pro and anti abortion, genital mutilation, academic feminism, Aboriginal education, women's health, and sexism within language. There are also papers and minutes of meetings of the A.C.T. women's organisation Women's Abode (1987-1992) (7 boxes).
MS Acc16.176 comprises daily diaries from 1953, 1957-2015; a large quantity of correspondence with Robin Doughty; and photographs, printed material and other papers relating to Kral's life, activities and interests, including her involvement with the Women's Electoral Lobby and the A.N.U. Centre for Continuing Education (10 boxes).
MS Acc20.020 comprises handmade daily diaries from 2016 to 2018 with typescript entries, associated notes, printed material and ephemera relating to Kral's relationships and health, various activities and events and reflections on feminism and ornithology (1 packet).
MS Acc23.098 comprises four handbound diaries with entries including details of appointments and social engagements. Also includes various ephemera collected during the years (2 folders).
Manuscript reference no. : MS 5262, MS Acc16.176, MS Acc20.020, MS Acc23.098.
Keywords: Kral, Shirley -- Archives; Women's rights -- Australia -- Archives; Feminists -- Australian Capital Territory -- Archives; Feminists